Study of Motivation on Employees in Achieving Organizations Goals: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Organizations develop strategies to compete in highly competitive markets and to increase their performance. Nevertheless, just a few organizations consider the human capital as being their main asset, capable of leading them to success or if not managed properly, to decline. If the employees are not satisfied with their jobs and not motivated to fulfill their tasks and achieve their goals, the organization cannot attain success. People have many needs that are continuously competing one with another.The present study was conducted on the Impact of Motivational Incentives on Employees’ Performance. The main objective of the study was to find out level of motivational incentives and to analyze the impact of those incentives on the performance of employees. The variables, which were the focus of the study, were level of job Satisfaction, level of performance, efficiency, organizational productivity, employees’ loyalty and professionalism